2015
DOI: 10.4238/2015.december.14.15
|View full text |Cite
|
Sign up to set email alerts
|

Association between the -607 C > A polymorphism in interleukin-18 gene promoter with gastrointestinal cancer risk: a meta-analysis

Abstract: ABSTRACT. The interleukin-18 (IL-18) gene -607 C/A polymorphism has been reported to be associated with gastrointestinal cancer, but there are conflicting results from previous studies on said topic. Therefore, the aim of this meta-analysis is to derive a more precise estimation of the association between the -607 C/A polymorphism in the IL-18 gene and gastrointestinal cancer risk. Literature searches of PubMed, Google Scholar, and Web of Science databases were carried out in 2015. Five studies were assessed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Instead, they collated data from several laboratories whose different platforms, protocols and data processing procedures question the significance (e.g. [8][9][10][11][12][13])…”
Section: Introductionmentioning
confidence: 99%
“…Instead, they collated data from several laboratories whose different platforms, protocols and data processing procedures question the significance (e.g. [8][9][10][11][12][13])…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated an association between IL18-607C/A and -137G/ C polymorphisms and the risk of many malignant tumors, such as esophageal cancer, gastrointestinal cancer, papillary thyroid cancer, hepatocellular carcinoma, prostate carcinoma, and oral squamous cell carcinoma (Liu et al, 2013;Singh et al, 2014;Bao et al, 2015;Chung et al, 2015;Dwivedi et al, 2015b;Li et al, 2015;Yao et al, 2015;Zhu et al, 2016). Singh et al (2014) performed a study on 272 patients with oral squamous cell carcinoma and 185 controls, and reported that the IL18-137G/C genetic variation was correlated with the progression of this cancer, but the -607C/A polymorphism was not.…”
Section: Discussionmentioning
confidence: 99%
“…Dwivedi et al (2015b) found that individuals harboring the GG genotype of IL18 could be diagnosed at an earlier stage than those with the CC genotype. Yao et al (2015) examined five studies comprising 1618 patients and 1155 healthy controls, and reported that the IL18-607C/A polymorphism was associated with a higher risk of esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%